Data Mining As A Technique for Business Process Redesign in University Library - Eka Miranda; Indrajani Indrajani (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
Traditional library catalogs have become inefficient and inconvenient in assisting library users. Readers mayspend a lot of time searching library materials via printed catalogs. Readers need an intelligent and innovativesolution to overcome this problem. The paper seeks to examine data mining technology, which is a goodapproach to fulfill readers’ requirements. The purpose of this paper is to suggest the use of data mining (DM) asa technique to support the process of redesigning a business by extracting the much-needed knowledge hiddenin large volumes of data maintained by the organization through the DM models. Data mining is considered thenon-trivial extraction of implicit, previously unknown, and potentially useful information from data. This paperanalyzes readers’ borrowing records using the techniques of data analysis, building a data warehouse, and datamining. The paper finds that after mining data, readers can be classified into different groups according to thepublications in which they are interested. The data mining results shows that all readers can be categorized intothree clusters; each cluster has its own characteristics. This phenomenon shows that these readers have ahigher preference for accepting digitized publications.Keywords: Digital-libraries, Data-mining, Data-warehouse